On-demand intelligent routing technology for deterministic network - Zhongli WU; Yuanyuan CAO; Wenrui HUANG; Bin DAI; Yijun MO (Dianxin kexue)
Deterministic network needs to ensure the deterministic transmission requirements of different applications in terms of delay, packet loss rate, jitter, throughput, and reliability.In response to the differentiated and deterministic network transmission requirements of applications, an on-demand intelligent routing framework OdR for deterministic network was proposed.Under the OdR framework, an on-demand intelligent routing algorithm named OdR-TD3 based on deep reinforcement learning was proposed, which generates routing strategies based on the deterministic QoS requirements of application traffic, to satisfy the applications’ requirements of deterministic network.The experimental evaluation results show the OdR-TD3 algorithm has a significant advantage over the DV algorithm and the SPF algorithm in terms of the achievement rate of deterministic QoS requirements.